2016
DOI: 10.1097/01.nep.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of High-Fidelity Simulation on Knowledge Gain and Retention

Abstract: Although current research suggests many positive outcomes with the use of high-fidelity simulation (HFS) in nursing education, little is known about the influence of HFS on knowledge retention. This quasiexperimental study examined the effects of HFS on student knowledge acquisition and retention, while validating the simulation quality with established tools on satisfaction, self-efficacy, educational practices, and simulation design. Results indicate that, although HFS had a statistically significant impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…We found evidence of a significant and considerable improvement from before to after training, which was in line with previous data in the literature. [4][5][6][7] Our data also corroborated studies that showed that simulation was essential for developing, testing, refining and implementing new workflows and protocols in healthcare. 8,10,11,18,19 This was also essential in the context of the COVID-19 pandemic, in which we trained healthcare professionals on the new protocol for safe and effective care of patients with COVID-19.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We found evidence of a significant and considerable improvement from before to after training, which was in line with previous data in the literature. [4][5][6][7] Our data also corroborated studies that showed that simulation was essential for developing, testing, refining and implementing new workflows and protocols in healthcare. 8,10,11,18,19 This was also essential in the context of the COVID-19 pandemic, in which we trained healthcare professionals on the new protocol for safe and effective care of patients with COVID-19.…”
Section: Discussionsupporting
confidence: 81%
“…Simulation training has been widely used for continuing professional development, in order to train healthcare professionals in relation to new systems, thereby enabling them to remain up-to-date regarding new demands and protocols within their clinical practice. [3][4][5][6][7] Simulation has played a key role in testing and implementing new workflow structures, new protocols and cognitive resources, 8 through offering participants the possibility to practice rare and critical events in a controlled environment. 9In the current pandemic, simulation has been shown to be useful for testing healthcare systems, processes and new protocols.…”
mentioning
confidence: 99%
“…The development of this LMS enabled the students to read and practice about IMI virtually which will help the student to expand their comprehension abilities and use their critical thinking to be able to perform IMI without the need to do real-life practice in the nursing lab, some studies like (16,17) found an enhancement in students' capability presentation, next simulation classes. Simulation brings enhancements to increasing knowledge (18) . And they can practice virtually administering of IMI using virtual simulation available in 3D.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, CSD 1 reflects the professionals' feeling of concern regarding their outdated information about the service protocols. According to the literature, 19 the knowledge acquired decreases over time and needs to be updated frequently. When the health professionals provide assistance when they are out of date, they can compromise the quality of the services and, above all, have a significant impact on the morbidity and mortality of the patients.…”
Section: /12mentioning
confidence: 99%